Mutants of the Pentose Phosphate Pathway in Aspergillus nidulans - Hankinson, Oliver (1974)
Mutants of the pentose phosphate pathway have been isolated in Aspergillus nidulans. These fail to grow on a variety of carbohydrates that are catabolized through the pentose phosphate pathway. They also grow poorly on nitrate and nitrite as sole nitrogen sources. The pentose phosphate pathway mutations have been assigned to two unlinked genes. Mutants with lesions in the pppB locus have reduced activities of four enzymes of the pentose phosphate pathway, of glucose-phosphate isomerase, and of mannitol-1-phosphate dehydrogenase. pppA(−) mutants have elevated activities of these same enzymes except for transaldolase, for which they have much reduced activity. Both classes of mutants accumulate sedoheptulose-7-phosphate to an extent that is increased considerably when nitrate is present in the medium. Nitrate does not cause an increase in accumulation of sedoheptulose-7-phosphate in double mutants which, in addition to the pppA1 mutation, carry a mutation that leads to the lack of nitrate reductase activity. These last results suggest that nitrate stimulates the flux through the oxidative pentose phosphate pathway, but that this stimulation depends upon the metabolism of nitrate.